Localization of angiotensin II type 1 receptor gene expression in rodent and human kidneys - Schrankl, Julia; Fuchs, Michaela; Broeker, Katharina; Daniel, Christoph; Kurtz, Armin; Wagner, Charlotte (American Journal of Physiology-Renal Physiology, 2021)
The kidneys are an important target for angiotensin II (ANG II). In adult kidneys, the effects of ANG II are mediated mainly by ANG II type 1 (AT1) receptors. AT1 receptor expression has been reported for a variety of different cell types within the kidneys, suggesting a broad spectrum of actions for ANG II. Since there have been heterogeneous results in the literature regarding the intrarenal distribution of AT1 receptors, this study aimed to obtain a comprehensive overview about the localization of AT1 receptor expression in mouse, rat, and human kidneys. Using the cell-specific and high-resolution RNAscope technique, we performed colocalization experiments with various cell markers to specifically discriminate between different segments of the tubular and vascular system. Overall, we found a similar pattern of AT1 mRNA expression in mouse, rat, and human kidneys. AT1 receptors were detected in mesangial cells and renin-producing cells. In addition, AT1 mRNA was found in interstitial cells of the cortex and outer medulla. In rodents, late afferent and early efferent arterioles expressed AT1 receptor mRNA, but larger vessels of the investigated species showed no AT1 expression. Tubular expression of AT1 mRNA was species dependent with a strong expression in proximal tubules of mice, whereas expression was undetectable in human tubular cells. These findings suggest that the (juxta)glomerular area and tubulointerstitium are conserved expression sites for AT1 receptors across species and might present the main target sites for ANG II in adult human and rodent kidneys.NEW & NOTEWORTHY Angiotensin II (ANG II) type 1 (AT1) receptors are essential for mediating the effects of ANG II in the kidneys. This study aimed to obtain a comprehensive overview about the cell-specific localization of AT1 receptor expression in rodent and human kidneys using the novel RNAscope technique. We found that the conserved AT1 receptor mRNA expression sites across species are the (juxta)glomerular areas and tubulointerstitium, which might present main target sites for ANG II in adult human and rodent kidneys.
CRIS-Team Scopus Importer:2021-04-23
Keywords: angiotensin II; angiotensin II type 1 receptors; kidney; renin-angiotensin-aldosterone system; RNAscope